Pelatihan Penyusunan Soal HOTS Berbasis Kurikulum Merdeka Belajar bagi Guru MTs. Muhammadiyah Tajurhalang Bogor - Hayun, Muhammad; Kartikasari, Pratiwi; Lubis, Adlan Fauzi; Sodikin, Sodikin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service aims to increase the understanding and competence of MTs Muhammadiyah Tajurhalang teachers in preparing HOTS questions based on the independent learning curriculum. The method for implementing this service used participatory training, with the stages of giving a pretest on the HOTS concept, training material and practice in preparing HOTS questions, giving a posttest, and giving an evaluation sheet for the implementation of the training. The data analysis technique employed descriptive statistical techniques using a percentage and graphic approach in presenting the data. This service partner was a teacher at MTs Muhammadiyah Tajurhalang Bogor. The results of this service showed that MTs Muhammadiyah Tajurhalang Bogor teachers had a good conceptual understanding of HOTS questions and increased skills in preparing HOTS questions based on the Merdeka curriculum, so that they could be practiced in every learning evaluation in class.